2018
DOI: 10.29220/csam.2018.25.1.001
|View full text |Cite
|
Sign up to set email alerts
|

On inference of multivariate means under ranked set sampling

Abstract: In many studies, a researcher attempts to describe a population where units are measured for multiple outcomes, or responses. In this paper, we present an efficient procedure based on ranked set sampling to estimate and perform hypothesis testing on a multivariate mean. The method is based on ranking on an auxiliary covariate, which is assumed to be correlated with the multivariate response, in order to improve the efficiency of the estimation. We showed that the proposed estimators developed under this sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Samawi and Abu-Dayyeh (2002) further extended this work by assuming the regressors to be random. Rochani et al (2018) demonstrated that the efficiency of multivariate regression estimator can be improved by using RSS. The literature on this topic is extensive in the last 50 years, for example see (Al-Saleh The first aim of this paper is to introduce DERSSmin (DERSSmax) sampling scheme, which is an extension to the modified ERSSmin (ERSSmax ) scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Samawi and Abu-Dayyeh (2002) further extended this work by assuming the regressors to be random. Rochani et al (2018) demonstrated that the efficiency of multivariate regression estimator can be improved by using RSS. The literature on this topic is extensive in the last 50 years, for example see (Al-Saleh The first aim of this paper is to introduce DERSSmin (DERSSmax) sampling scheme, which is an extension to the modified ERSSmin (ERSSmax ) scheme.…”
Section: Introductionmentioning
confidence: 99%